PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MD CELL SAMARINDA - Marten Apuy; Suarno; Keshia Putri Couwindra (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
The Influence of Leadership and Compensation on Employee Performance of MD Cell Samarinda (Under the guidance of Benediktus Sunarsi and Sudirman). The study is to determine whether "Does Leadership and Compensation have a partial and simultaneous effect on Employee Performance at MD Cell Samarinda?". The respondents are 40 empolyees at MD Cell Samarinda with saturated sampling technique. Data collection methods consist of observations, interviews, questionnaire disseminations, and documentations. The analytical tools used in this study used multiple linear regression analysis models, partial correlation coefficients, multiple correlation coefficients, determination coefficients, and hypothesis testing using t test and F test which were processed using IBM SPSS version 25 program. With test the instrument and test the classical assumptions. The result of the Multiple Linear Regression analysis is ????̂ 23,021+0,992 X1+0,554 X2, means that Leadership (X1) and Compensation (X2) affect Employee Performance (Y). Among the variables of Leadership and Compensation, it shows Leadership with a Partial Determination value is 0.409 or 40% which means the most dominant in influencing Employee Performance. On the other hand, Compensation has a Partial Determination value of 0,268 or 26% on the Employee Performance. From the results of the t test, it was found that it has a significant impact between Leadership on Employee Performance (3,724>2,024), and between Compensation on Employee Performance (3,455>2,024). Furthermore, from the results of test F, it was found that Leadership and Compensation simultaneously affect the Employee Performance (8,301>3,25).